A role of anti-Mullerian hormone in external genital endometriosis - A. S. Molotkov; M. I. Yarmolinskaya (IRBIS LLC, 2021)
To understand a role for anti-Muller hormone (AMH) in the development and course of genital endometriosis, we sought out for and analyzed scientific papers in open electronic sources: PubMed, Scopus, eLibrary. We review a role of AMH in females as well as its importance in functioning of the reproductive system, noting that in developing external genital endometriosis its blood level decreases that may either due to ovarian damage or one of the links in the disease pathogenesis. Potential negative consequences of surgical interventions for ovaries as well as means for their prevention are described.